Technology use and constituting structures: accounting for the consequences of information technology on police organisational change - Willis, James J. (Policing and society, 2020)
The influence of information technology on organisational change has long been a concern in policing. Despite the assumption that technology holds great potential for improving police performance, studies suggest that technology delivers mixed results. In this article, we use a theoretical model well-known in studies on organisations and information systems but less familiar in criminal justice. The structurational model of information technology helped explain the complex processes underlying the organisational effects of a new records management system (RMS) in a single police agency. Using interviews, focus groups, and an agency-wide survey, we found that various designer and user groups interpreted and interacted with the RMS differently. Thus the same type of information technology led to the development of different ‘technologies-in-practice.’ Despite the agency’s concerted efforts to facilitate the RMS’s acceptance, these differences between groups led to unintended consequences, including reinforcing the traditional divide between street cops and management cops.